Two interval type 2 fuzzy TOPSIS material selection methods. (25th December 2015) - Liao, T. Warren
Abstract: Material selection is very important in engineering design. Material selection methods utilizing fuzzy set theory have gradually gained acceptance because of their capabilities in handling impreciseness inherent in measuring material properties. Past studies are all based on type 1 fuzzy sets. This paper presents two interval type 2 fuzzy multi-attribute decision making methods for material selection. Rather representing uncertainty in trapezoidal type 1 fuzzy sets, this paper represents uncertainty in measurement, preference, judgment, or prediction in terms of trapezoidal interval type 2 fuzzy sets instead. This representation allows higher degree of impreciseness by specifying membership value as an interval rather than as an exact value. The two new methods presented in this paper are extended from two existing TOPSIS methods based on type 1 fuzzy set. They differ mainly in the stage when defuzzification is carried out and other details. Note that the two existing type-1 fuzzy based TOPSIS methods assume no knowledge about desirable material property values. It is shown in this paper that such methods might lead to the selection of undesirable materials. An example is used to illustrate the working of the two new methods, followed by discussion about the effects of some relevant factors. Ideas for extending this study are given in the conclusions. Graphical Abstract: Sketch of the proposed two Interval Type-2 fuzzy TOPSIS material selection methods. Highlights: Develop two TOPSIS material selection methods based on IT2 FN Stress the importance of including desirable properties Discuss the effect of various components of the proposed methods